"Young singers get musical help from Santa Claus" (Philadelphia Evening Bulletin, 1955)
"Children of the St. Paul's Lutheran Church choir surround Santa Claus as the visitor from the North Pole provides accompaniment for a program of Christmas carols in the lobby of the Benjamin Franklin Hotel." With clipping